Core-satellite BaTiO3@SrTiO3 assemblies for a local compositionally graded relaxor ferroelectric capacitor with enhanced energy storage density and high energy efficiency. Issue 4 (8th December 2014) - Wu, Longwen; Wang, Xiaohui; Gong, Huiling; Hao, Yanan; Shen, Zhengbo; Li, Longtu
Abstract : Facile sol-precipitation fabrication of core-satellite BaTiO3 @SrTiO3 assemblies for a local compositionally graded capacitor. Abstract : Dielectric capacitors with high energy density and low energy loss are of great importance in high power electric and electronic systems. Traditional BaTiO3 (BT) or its solid solutions have been widely explored as high energy density materials owing to their notably high dielectric constants. However, these materials often suffer from significant drawbacks of strong dielectric nonlinearity, low breakdown strength and high hysteresis loss, limiting the energy storage density and energy utilization efficiency. In this study, by using core-satellite structured nanocubic SrTiO3 (ST) decorated BT assemblies, a composite capacitor with enhanced breakdown strength and weaker dielectric nonlinearity was successfully fabricated in contrast with the pure ferroelectric BT ceramic, resulting in elevated energy storage density and high energy efficiency as extracted from the polarization-electric field loops. The mechanism behind the improved electric and dielectric performances was discovered to be the remarkable suppression of grain size owing to the existence of the ST nanocubes and also the ferroelectric relaxor behaviors arising from the local compositionally graded structure due to the controlled sintering and modulated diffusion of Sr. This work provided a new approach for fabrication of dielectric materials with promising high energy density and low loss.